2021
DOI: 10.3390/ijerph18063314
|View full text |Cite
|
Sign up to set email alerts
|

A School-Level Examination of the Association between Programs and Policies and Physical Activity Outcomes among Females from the COMPASS Study

Abstract: (1) The majority of Canadian youth are not meeting physical activity guidelines, and more female than male youth are falling short of these recommendations. School programs and policies are a viable strategy to improve youth physical activity. However, they may differentially affect female and male activity. This study aimed to examine school-level differences in physical activity outcomes among male and female students and to explore how school programs and policies associate with school-level physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Response rates in 2017/18 and 2018/19 were 81.8% and 84.2%, respectively, with non-response being mainly due to absenteeism or scheduled spare time during data collection. [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Response rates in 2017/18 and 2018/19 were 81.8% and 84.2%, respectively, with non-response being mainly due to absenteeism or scheduled spare time during data collection. [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The differences between the level of engagement of males and females were reported across 7 studies. It was indicated that females were falling short to meet the guidelines in physical activity, and they were more problematic in experiencing barriers to physical activity, increase in school works was negatively associated with their physical activity (Burns et al, 2021), and a steep decline in physical activity during adolescence (Lau et al, 2019), lean body mass significantly decreasing in female (Oshita & Myotsuzono, 2021). Females also tend to experience more injury compared to males (Post et al, 2020).…”
Section: Retrieval Of Potential Recordsmentioning
confidence: 99%
“…Females also tend to experience more injury compared to males (Post et al, 2020). Meanwhile, males accrued greater physical activity minutes and strength training days (Burns et al, 2021), and were more physically active (Chen et al, 2021). Contrarily, females' enjoyment in physical activity is positively associated, with motivation to participate if they have ambassadors (Burns et al, 2021), higher adoption of health prevention behaviors (Kim et al, 2020), and youth sports participation could be more important among females (Kwon et al, 2021).…”
Section: Retrieval Of Potential Recordsmentioning
confidence: 99%
See 2 more Smart Citations